Alcohol use disorder severity and reported reasons not to seek treatment: a cross-sectional study in European primary care practices - Probst, Charlotte (Subst Abuse Treat Prev Policy, 2015)
BACKGROUND: Alcohol use disorders are among the mental disorders with the lowest treatment rates. Increasing the treatment rates requires insight on the reasons why patients do not seek treatment. This study examined self-reported reasons for not seeking treatment and their association with alcohol use disorder severity among primary health care patients diagnosed with an alcohol use disorder. METHODS: Alcohol use disorders, health service utilization, and reasons for not seeking treatment were assessed via interviews on regionally representative samples of primary care patients from 6 European countries (Italy, Germany, Hungary, Latvia, Poland and Spain, total N = 9,098). Additionally, general practitioners had to fill in a questionnaire assessing their patients’ alcohol use and alcohol use disorders. A multinomial logistic regression was performed to investigate the association between reasons for not seeking treatment and alcohol use disorder severity. RESULTS: Of 1,008 patients diagnosed with an alcohol use disorder (via general practitioner or patient interview) in the past 12 months, the majority (N = 810) did not receive treatment and 251 of those gave a reason for not seeking treatment. The most frequent reason was ‘lack of problem awareness’ (55.3 % of those who responded), the second most common response was ‘stigma or shame’ (28.6 %), followed by ‘encounter barriers’ (22.8 %) and ‘cope alone’ (20.9 %). The results indicated lower probabilities of reporting ‘denial’ and higher probabilities to report ‘encounter barriers’ as alcohol use disorders severity increases. However, both trends were discontinued for patients with severe alcohol use disorders. CONCLUSIONS: Particularly at lower levels of alcohol use disorder severity, a lack of problem awareness prevents patients from seeking treatment. Routinely alcohol consumption monitoring in primary care practices could help primary and secondary prevention of alcohol use disorders and increase treatment coverage. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13011-015-0028-z) contains supplementary material, which is available to authorized users.